2016
DOI: 10.37828/em.2016.7.9
|View full text |Cite
|
Sign up to set email alerts
|

Silks and Silk-Producing Organs of Neotropical Tarantula Avicularia Metallica (Araneae, Mygalomorphae, Theraphosidae)

Abstract: Silks and silk-producing organs of the theraphosid species Avicularia metallica were studied using scanning electron microscopy. The spinning apparatus is made up of two pairs of spinnerets located at the end of the ventral side of the opisthosoma. Both pairs of spinnerets are equipped with spigots (modified setae), i.e. external outlets of silk-producing glands which, in the case of posterior lateral spinnerets, are present on all three segments.The secreted silk, which hardens when exposed to air, is process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The absence of silk threads variety is compensated by the large size of the spiders themselves. Mygalomorphae possess an enlarged abdomen [ 57 ], due to which they can produce enough cobwebs, for example, to create a large dwelling. Based on observations of adult spiders from the family Dipluridae ( Linothele fallax ) at the local insectarium in SCAMT Institute, it was found that one adult spider can secret up to 10 mg of cobwebs per week.…”
Section: Spider Silks Characterization and Propertiesmentioning
confidence: 99%
“…The absence of silk threads variety is compensated by the large size of the spiders themselves. Mygalomorphae possess an enlarged abdomen [ 57 ], due to which they can produce enough cobwebs, for example, to create a large dwelling. Based on observations of adult spiders from the family Dipluridae ( Linothele fallax ) at the local insectarium in SCAMT Institute, it was found that one adult spider can secret up to 10 mg of cobwebs per week.…”
Section: Spider Silks Characterization and Propertiesmentioning
confidence: 99%